Mutilation by cancer: articulating health, psychology and education - Mendes da Rocha, Magna Celi; Makino Antunes, Mitsuko Aparecida (O Mundo da Saúde, 2012)
This article is part of the results of a Master in Education research (Psychology of Education) in PUC-SP, which aimed to understand the constitution of the identity of pupil mutilated by childhood cancer, with a focus on the process of school placing and re-placing on the basis of inclusive education guidelines. The theoretical perspective that bases the category of Identity in this research was that of Ciampa, which, in the field of Social Psychology, studies Identity as a synthesis of multiple determinations. Identity is understood as metamorphosis, an expression used to suggest the idea of movement and continuous transformation as a constituent of this process. The research subject was a survivor of childhood cancer, with a visible physical mutilation, that that passed by a process of re-insertion to the school environment after the end of treatment. This is a qualitative research characterized as a case study using the technique of life history narrative, seeking to understand the transformations in the identity of a subject considered emblematic in the process of school inclusion. Data demonstrate that, from the point of view of schooling, no insertion have happened, but rather an integration process. However, the subject did not suffer exclusion; for him, inclusion in a sport activity determined the process of overcoming his condition towards emancipatory metamorphosis.